A proposal for an open-source financial risk model. Issue 3 (8th July 2014) - Ho Hwang, Jong
Abstract : Purpose: – The purpose of this paper is to present a policy proposal for building a new framework for gathering, measuring and disclosing financial risk information in the global economy. Design/methodology/approach: – The paper examines the current state of the financial risk framework, notes its advantages and disadvantages and proposes a new construct that aims to address some of the shortcomings that are currently in place. The goals of a robust financial risk model are examined to determine the design of the proposed risk framework. Findings: – The proposed open-source financial risk model separates the dual function that internal risk models perform within financial institutions, first to attempt to optimize the risk–return profile of mostly private economic rent-seeking entities, and second to maximize safety and soundness considerations for the public which is at risk of bearing the consequences of financial actors. Practical implications: – The model allows widespread use of robust financial risk models. Social implications: – The model enables a more transparent and democratic process for risk management. Originality/value: – The study proposes a new global supervisory framework. Practical implications: – The model allows widespread use of robust financial risk models. Social implications: – The model enables a more transparent and democratic process for risk management. Originality/value: – The study proposes a new global supervisory framework.